OP0243 Prevalence of inflammatory and chronic changes suggestive of axial spondyloarthritis in magnetic resonance images of the axial skeleton in individuals <45 years in the general population as part of a large community study (SHIP). (12th June 2018) - Baraliakos, X.; Feldmann, D.; Ott, A.; Schmidt, C.O.; Albers, M.; Richter, A.; Braun, J.
Abstract : Background: Magnetic resonance imaging (MRI) is crucial for classification and diagnosis of axial spondyloarthritis (axSpA). Characteristic MRI lesions of axSpA are bone marrow oedema (BME) or structural fatty lesions (FL) of the sacroiliac joints (SIJ) and spine. However, the specificity of these lesions has been questioned, since patients with chronic back pain but no axSpA may also have a positive MRI, as shown in recent cohort studies. Objectives: To investigate the prevalence of BME and FL on MRI of the spine and the SIJ in the general population. Methods: Volunteers<45 years of the population based Study of Health in Pomerania (SHIP) 1, 2 underwent MRI examinations of the spine (sagittal orientation, T1 and T2 MRI sequences) and the SIJ (coronal orientation, STIR sequences), independently of clinical symptoms. Two trained readers blinded for age and gender of the examined persons evaluated the prevalence of BME (SIJ and spine) and FL (spine) suggestive of axSpA using the ASAS definitions: a lesion in the SIJ was considered positive if located periarticularly and in the middle part of the joint and A lesion in the spine was considered positive if detected at the edge of the vertebral body). Clearly degenerative lesions involving the vertebral endplate or being accompanied by abnormalities of the intervertebral disc (protrusion or prolapse) were not counted. Results: A total of 802 complete MRI sets (spine and SIJ) of 394 male (49.1%) and 408 female volunteers (50.9%) was evaluated. The mean age of all patients was 37.5±6.2 years. BME in the SIJ suggestive of axSpA were found in 144 individuals (18%), with an equal distribution between males (n=74, 18.8%) and females (n=70, 17.2%). A similar pattern of BME was found in the spine, again with no differences between males and females. However, the location of the lesions was different: 9.5% had ≥1 lesion in the cervical, 18.6% in the thoracic and 7.4% in the lumbar spine. Overall, 88.6% male and 84.6% female volunteers were found to have ≥1% and 54.6% male and 46.1% female volunteers were found to have at ≥3 positive spinal lesions in any spinal region. In comparison, the prevalence of FL was higher (36.7% volunteers in the cervical, 72.4% in the thoracic and 52.7% in the lumbar spine). Overall, 86.5% volunteers were found to have ≥1% and 50.2% volunteers were found to have ≥3 positive spinal lesions in any spinal segment. Logistic regression analysis showed that age was the only demographic characteristic that independently contributed to the occurrence of both BME (RR=1.22, 95% CI: 1.03 to 1.46, p<0.025) or FL ((RR=1.12, 95% CI: 1.07 to 1.19, p<0.001). Conclusions: In this large population-based study with healthy volunteers a relatively high prevalence of inflammatory and structural MRI lesions was found. Whether these lesions are to be explained by mechanical stress needs to be further studied. The high prevalence of BME and FL in the axial skeleton in the general population indicates a limited diagnostic value of these MRI findings. Thus, those should be interpreted with caution in relation to diagnosis, classification and assessment of disease activity. References: [1] Bundesgesundheitsbl2012. [2] Völzke H, et al. Int J Epidemiol2011. Disclosure of Interest: None declared